The influence of socio-cultural conditions on inter-local collaboration: Rethinking resource-dependency theory from the lessons of Thailand - Pobsook Chamchong (2020)
© 2019 by De La Salle University. This study aims to map out the practices of inter-local collaboration in Thailand and understand the conditions that facilitate the formation and sustainability of the existing collaboration. The mixed methods research design was employed by which in-depth interviews of specific cases were adopted to elaborate on the statistical findings. The study found that, for the most part, inter-local collaboration in the largest region of the country was asymmetric. The case study findings undermine resource dependency theory, given that councils with larger resources can become locked-in to disadvantageous relationships with, and be controlled by, smaller councils with fewer resources. This is because asymmetric relationships and vertical forms of inter-local collaboration were facilitated by the strong hierarchical social system prevalent in Thai culture and the Thai local government system, in which the “big brother” council is expected to help smaller “new-born” councils. This influence of socio-cultural conditions on inter-local collaboration, thus, should be taken into account in existing theories of inter-local collaboration so that they move beyond consideration only of legal-institutional perspectives.